Implementation of Joyful Learning With Child Friendly School Web Application in Depok - El Khuluqo, Ihsana; Zuadkia, Ivan (EARR (Educational Administration Research and Review), 2023)
This study aims to analyze the extent to which the adoption of child-Friendly Schools in the Village of Tugu, Kecamatan Cimanggis Depok through the Application use of Child-Friendly Schools. The application of Child-Friendly Schools created as a research tool refers to the rules of the government regarding the implementation of Child-Friendly Schools. The research method used is research methods a Mix Method. Research Mix Method can describe the results of research with accuracy refers to the accurate data given to the school through Application of Child Friendly School. This study was followed by the 9 public Elementary Schools as research subjects. The results showed that most of the State primary School in the Village of Tugu has met the requirements for becoming a Child Friendly School. In the application of Child-Friendly Schools need to be implemented because support of safety and comfort in the process of teaching and learning activities the Implementation of An CFS includes the planning and implementation of the review of the learning process and infrastructure facilities at the elementary school in the Village of Tugu, Depok City. Supporting factors include the school, community and local government in the implementation of the CFS review of the process of teaching and infrastructure at the State primary School in the Village of Tugu, Depok City. Inhibiting factors include the school, community and local government in the implementation of the CFS review of the process of teaching and infrastructure at the State primary School in the Village of Tugu, Depok City.